Incidence of injuries in French professional soccer players - Dauty, M.; Collon, S. (International Journal of Sports Medicine, 2011)
In this prevalence cohort study, injuries sustained during 15 seasons in a professional soccer team were investigated according to the different soccer seasons, number of matches per season, month the injury occurred, location, severity, playing position and the team's rank at the end of the French professional championship. Altogether, 903 injuries in 173 professional soccer players were reported. Injury incidence per 1 000 h of exposure during matches and training was 4.7±5. This incidence did not vary significantly between seasons. However, injury incidence increased after the year 2003 and constantly exceeded 4.2. In the same way, after 2002 muscle injury incidence always exceeded 2 per 1 000 h of exposure. Injury incidence peaked during the month of January. Hamstring muscle injury represented the most frequent injury. No difference in injury incidence was found according to the playing position or to the season whether the team participated or not in the European cup. No correlation was found with the team's rank at the end of the French championship. This study highlighted no significant variation on injury incidence over a 15-season period except for the muscle injury rate in high level soccer players.